دور اللغة في تعیین معنی الشرعي من القرآن الکریم: Role of Language in Defining the Meanings of Sharī ̒a in the Holy Quran (Al-Qamar, 2020)
The article "The Role of Arabic Language in defining the meanings of Sharia in the Holy Quran" Brings to light that the greatness of the Holy Quran lies in its worth as a Words of God and also as a book of life ideology. Regardless of Muslims lingual, racial and cultural differences, they are, at all, from one community of believers. This community is based on their faith in One Almighty God Allah and His guidance. Thus, it is the language of Arabic that joins the different communities of believers. Allah revealed final revelation, the Quran to mankind 1400 years ago in the Arabic language. The original Arabic text of the Holy Quran has been preserved by Allah from any type of amendment. Quran has been translated into various languages based on its original Arabic text. In order to fully understand the magnificent words of Allah, Muslims try to learn and understand Arabic language in its classic form. Since it is very important to understant Arabic, most Muslims try to learn at least the basics of Arabic language. Many of them study and learn its classic liturgical form, in order to deep understand the text of Holy Quran in its original form. The differences in the interpretations of the Quranic commandments are found frequently in the Islamic jurists and the scholars. Hence, Conflict occurs between scholars due to different linguistic rhetoric of language. It proves that in the derivation of the Quranic laws, the role of Arabic language cannot be ignored.
Keywords: Language; Role Sharī ̒a; Holy Quran